Characterization of vertically oriented carbon nanotube arrays as high-temperature thermal interface materials. (March 2017) - Hao, Menglong; Huang, Zhengxing; Saviers, Kimberly R.; Xiong, Guoping; Hodson, Stephen L.; Fisher, Timothy S.
Highlights: Carbon nanotube arrays are tested as thermal interface materials at up to 700 °C in vacuum. A decreasing trend in total thermal interface resistance is observed with increasing temperature. Temperature dependence suggests that contact resistance prevails over bulk resistance. Excellent thermomechanical compliance is demonstrated. Abstract: Carbon nanotube arrays hold much potential for high-temperature thermal interface applications that require thermal stability and mechanical compliance. A 1D reference bar test rig designed for measurements at and substantially above room temperature is used to perform thermal cycling tests on CNT arrays and to measure their thermal interface resistance at temperatures up to 700 °C. The CNT arrays are synthesized and tested with both thermomechanically matched (Cu-Cu) and mismatched (alumina-Cu) interfaces to examine their mechanical compliance. For both cases, a moderate decrease in thermal interface resistance (TIR) occurs from room temperature to 700 °C. The results reveal good cyclic stability of CNT arrays in both cases, confirming their ability to accommodate large thermomechanical mismatch. Post-mortem analysis indicates that CNT free ends conform to the opposing Cu surface. In the Cu-Cu interface, only compressive deformation of the CNT arrays is observed. In the alumina-Cu interface, more complex thermomechanical deformation occurs that is hypothesized to be a combined effect of compressive loading and shear stress.